Added Benefit of Stent Retriever Technology for Acute Ischemic Stroke: A Pooled Analysis of the NINDS tPA, SWIFT, and STAR Trials. Issue 3 (September 2015) - Saposnik, Gustavo; Lebovic, Gerald; Demchuk, Andrew; Levy, Elad I.; Ovbiagele, Bruce; Goyal, Mayank; Johnston, S. Claiborne
Abstract : BACKGROUND: Endovascular treatment is increasingly being used in acute stroke care. However, although stent retrievers show improved flow restoration rates, their clinical benefits have been uncertain. OBJECTIVE: To assess the incremental effect of using stent retrievers compared with intravenous tissue plasminogen activator (IV tPA; alteplase) alone or placebo/control. METHODS: We conducted a pooled analysis of 4 studies using stent retrievers (Solitaire), IV tPA, or placebo/control. We applied the ischemic stroke risk score (www.sorcan.ca/iscore ) to each participant to adjust for differences in baseline characteristics. We used a shift analysis to account for the potential benefits across the entire modified Rankin scale score at 90 days, adjusting for time-to-treatment, baseline Alberta Stroke Program Early CT score, and ischemic stroke risk score. RESULTS: Of the 915 participants in this analysis, 312 (34.1%) patients received placebo, 312 (34.1%) received tPA alone, 131 (14.4%) received stent retrievers alone, and 160 (17.5) received combined therapy (IV tPA plus stent retrievers). The shift analysis revealed that more patients remained independent at 90 days if receiving stent retrievers alone (number needed to treat 3.5) or combined with tPA (number needed to treat 3.1) compared with tPA alone. After adjustment, participants receiving stent retrievers alone (odds ratio, 2.95; 95% confidence interval, 1.48-5.89) or combined with tPA (odds ratio, 4.45; 95% confidence interval, 2.40-8.27) were more likely to be independent at 90 days compared with tPA alone. CONCLUSION: Patients with acute ischemic stroke who received IV tPA or revascularization therapies had a higher likelihood of achieving independence at 3 months. Stent retriever technology combined with tPA was associated with the greatest benefit compared with placebo, tPA alone, or endovascular therapy alone. ABBREVIATIONS: ASPECTS, the Alberta Stroke Program Early CT score ESCAPE, The Endovascular Treatment for Small Core and Proximal Occlusion Ischemic Stroke iScore, ischemic stroke risk score IV, intravenous MR CLEAN, Multicenter Randomized Clinical trial of Endovascular treatment for Acute ischemic stroke in the Netherlands mRS, modified Rankin scale NIHSS, National Institutes of Health Stroke Scale NINDS, National Institute of Neurological Diseases and Stroke sICH, symptomatic intracerebral hemorrhage STAR, the Solitaire Flow Restoration Thrombectomy for Acute Revascularization SWIFT, Solitaire flow restoration device vs the Merci Retriever in patients with acute ischemic stroke tPA, tissue plasminogen activator (alteplase) WHO, World Health Organization Abstract : Supplemental Digital Content is Available in the Text.